Analysing Southern African food security: assessing the New Variant Famine hypothesis - Riet, G. van (Koers, 2007)
This article investigates the New Variant Famine (NVF) hypothesis coined by Alex De Waal during the 2001-2003 Southern African food security crisis, as a tool for analysing food insecurity in the region. The NVF hypothesis depicts a protracted and extensive famine from which there is very little chance of recovery, in which HIV and AIDS are central to the widespread suffering of people. The author suggests that the role of HIV and AIDS on food security be considered as one contributing factor to a dynamic process(es) of vulnerability and not viewed in isolation. In addition it is suggested that analyses focus on underlying processes driving vulnerability and not on specific instances of “famine” or crisis.